Analysis of the quality of technical execution of high hand strokes in school category badminton athletes - Yarisel Cardentey Figueroa; Tania Rosa García Hernández; Ayran Arencibia Moreno (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The practice of badminton since its beginnings in the high performance in the province of Pinar del Río, has managed to maintain a systematic work and with results that guarantee the stay of Pinar del Río athletes in the national elite, mainly in the double and mixed modality, however in the evaluation of the results of the pedagogic-technical tests and evaluations of the pedagogic objectives at national level are currently evaluated from Mal. With the objective of knowing such behavior, a meticulous study was made of the particularities of the technical execution of high hand strikes, which turns out to be the technique most affected according to observations made in training sessions and development of competencies. The research was developed in the seven athletes of the school category of the Eide "Ormani Arenado Llorch" from Pinar del Río. Through the interview and the observation as scientific methods, it was possible to verify the level of technical execution of high hand strokes in the badminton athletes of school category, detecting deficiencies that attempt to obtain superior competitive results.